Sometimes here, sometimes there—Differential effects of social challenge and hindrance stressors depending on the work location - Rigotti, Thomas; Schilbach, Miriam; Kern, Marcel (Frontiers in Organizational Psychology, 2024)
Introduction As a result of the COVID-19 pandemic, the number of employees working from home has more than tripled in Germany from 2019 to 2022. While earlier research on remote work primarily focused on discerning variations among employee groups, this study delves into the realm of intra-individual effects. Specifically, we investigate how social stressors relate to exhaustion and positive affect at the end of the day within the context of different work settings. Methods This research draws insights from a sample comprising 99 employed individuals who diligently responded to surveys over a span of up to 10 working days (with an average of 6 days) after work and prior to bedtime. Results Although the absolute level of encountered social stressors exhibited no noteworthy difference between working at home or the premise of the employer, the relationship to exhaustion was moderated by the work location. Remarkably, the positive link between challenge-oriented social stressors and exhaustion manifested solely on days spent working from home. In contrast, social hindrance stressors exhibited a positive association with exhaustion exclusively on days when employees were operating within the organizational premise. Discussion These findings offer preliminary indications that the significance of specific stressors might indeed fluctuate based on the physical location of work. In essence, this study sheds light on the nuanced interplay between stressors and employee wellbeing, thereby adding depth to our comprehension of the remote work landscape.